AAMP98 ニ オケル オンシツ コウカ キタイ ノ コウクウキ カンソク - 菅原, 敏; スガワラ, サトシ; 森本, 真司; モリモト, シンジ; 青木, 周司; アオキ, シュウジ; 中澤, 高清; ナカザワ, タカキヨ; Sugawara, Satoshi; Morimoto, Shinji; Aoki, Shuji; Nakazawa, Takakiyo (2002)
P(論文) 北極域の対流圏および成層圏下部における温室効果気体の分布を明らかにするため，北極圏航空機観測計画（AAMP 98）の 一環として大気試料のサンプリングが実施された． これらの試料は，CO2,CH4, N2O、COの各濃度，また CO2の炭素・酸素同位体比，CH4の炭素同位体比の分析に用いられた．スピッツベルゲンとパ口 ーにおける鉛直方向の観測では，CO2,CH4, N20, COの各濃度が対流圏界面付近から成層圏下部にかけて急激に減少していることが確認された．アンカレッジとスピッツベルゲンの間の成眉圏下部では，CH4 濃度とそのδ^13Cとの聞に明瞭な負の相関が見られ，見かけの同位体分別係数は1.013 （士0.003）であった．この変動がCH4の反応消滅によって引き起こされたと仮定した場合，それに対するClの寄与は 12–17%であると推定された． Air samples collected using aircraft during the Arctic Airborne Measurement Program 1998 (AAMP 98) were analyzed for the CO2, CH4, N20, and CO concentrations as well as for the carbon and oxygen isotopic ratios，δ^13C and δ^18O,of CO2, and δ^13C of CH4. The vertical distributions of CO2, CH4, N2O, and CO concentrations showed rapid decreases from the tropopause to the lower stratosphere over Ny-Alesund and Barrow. From the measured values of the CH4 concentration and δ^13C, the apparent carbon isotopic fractionation factor was estimated to be 1.013 （士0.003) in the lower stratosphere. The contributions of the chemical CH4 reactions with OH, O(^1 D) and Cl were examined by using the isotopic fractionation factors. It is suggested from this examination that the contribution of the reaction of CH4 with Cl is 12-17%. departmental bulletin paper